Temporal relationship between hospital admissions for pneumonia and weather conditions in Shanghai, China: a time-series analysis - Yuan Liu; David Rogers; Yue Zhang; Haidong Kan; Weibing Wang; Jianming Xu; Renjie Chen; Xiaofang Ye; Li Peng (BMJ Open)
Objectives To explore the association between weather conditions and hospital admissions for pneumonia in Shanghai.Design A time-series analysis was performed for a period of 4 years (January 2008–December 2011). A generalised additive model was used to calculate the relative risks.Setting Shanghai, China.Participants All daily hospital admissions for pneumonia were obtained from the Shanghai health insurance system between 1 January 2008 and 31 December 2011 (n=99 403).Results The relationship between the mean temperature and pneumonia hospital admissions followed a V-shaped curve, with an optimum temperature (OT) at 13°C. When the mean temperature was below the OT, a 1°C decrease corresponded to a 4.88% (95% CI 2.71% to 7.09%) and 5.34% (95% CI 2.04% to 8.74%) increase in pneumonia hospital admissions in lag 4 using a single-day lag structure and lag 0–7 using a multiday lag structure. When the mean temperature ≥OT, no adverse effects from the temperature on pneumonia hospital admissions were found. The magnitude of the effects of temperature varied across gender and age groups. Hospitalisations for pneumonia increased by 15.99% (95% CI 0.06% to 34.46%) in the cold period.Conclusions Cold temperature may be one of the important risk factors for pneumonia hospitalisations. Prevention programmes are needed to reduce the impact of cold temperature on pneumonia hospitalisations such as developing a weather warning system within a wide public health context.